ORGANIZATIONAL CITIZENSHIP BEHAVIOR TERHADAP KINERJA KARYAWAN, KEPUASAN KERJA SEBAGAI VARIABEL INTERVENING PADA PT. SWADAYA MUKTI PRAKARTA, KETAPANG - Ekobelawati, Fransiska; Marjono, Marjono; Iswanto, Iswanto; Ishak, Ishak (Jurnal Ekonomi STIEP, 2023)
This research investigates the significant relationship among Organizational Citizenship Behavior (OCB), employee performance, and job satisfaction within the context of PT. Swadaya Mukti Prakarta. The study employed statistical analysis, including a paired t-Test for Means, to assess the mean differences between OCB and employee performance. The findings revealed a substantial positive correlation (Pearson's correlation coefficient of 0.893) between OCB and employee performance, indicating that higher levels of OCB among employees are associated with increased performance levels. Furthermore, the research examined the relationship between job satisfaction and employee performance. The results demonstrated a strong positive correlation (Pearson's correlation coefficient of 0.931) between job satisfaction and employee performance, emphasizing the critical role of job satisfaction in enhancing overall employee performance. Additionally, the validity and reliability of the measurement instruments were tested. The study confirmed the validity of the survey questions for all three constructs (OCB, employee performance, and job satisfaction) and established satisfactory reliability for the measurements. In conclusion, this research highlights the significant impact of OCB on employee performance and underscores the importance of fostering OCB and job satisfaction in enhancing organizational effectiveness. These findings offer valuable insights for organizations seeking to improve their employees' performance and overall job satisfaction.